Study on the Mechanism of Financial Management Element Reconstruction Empowered by Artificial Intelligence in Enterprises - Kuierban, Dilireba (International Journal of Social Sciences and Public Administration, 2025)
With the rapid development of artificial intelligence (AI) technology, enterprise financial management is facing unprecedented opportunities and challenges. Traditional financial management models are no longer sufficient to meet the increasingly complex needs of modern enterprises, especially in areas such as data analysis, decision support, and risk management. This paper explores how AI can empower various elements of financial management and constructs a mechanism for restructuring these elements based on AI. Through literature review and case analysis, key issues in traditional financial management, such as inefficiency in manual operations and delayed decision-making, are identified. The study finds that AI has significant advantages in improving data processing efficiency, optimizing financial decision support, and enhancing risk forecasting and control. Finally, the paper proposes a restructuring framework for the transformation of enterprise financial management, providing theoretical support and practical guidance for achieving intelligent financial management.